You should solve the indefinite integral using substitution, hence, you should come up with the following substitution such that:

`1 + tan x= u => (dx)/(cos^2 x) = du`

`int (dx)/((cos^2 x)sqrt(1 + tan x)) = int (du)/(sqrt(u)) `

`int (dx)/(cos^2 x)sqrt(1 + tan x) = int u^(-1/2) du`

`int u^(-1/2) du = (u^(-1/2+1))/(-1/2+1) + c`

`int u^(-1/2) du = 2u^(1/2) + c => int u^(-1/2) du = 2sqrt u + c`

Substituting back `1 + tan x` for u yields:

`int (dx)/((cos^2 x)sqrt(1 + tan x)) = 2sqrt(1 + tan x) + c`

**Hence, evaluating the given integral using substitution yields `int (dx)/((cos^2 x)sqrt(1 + tan x)) = 2sqrt(1 + tan x) + c` .**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now